Group Interaction Method Based on Wireless Sensor Network - Wu Qun; Zhou Haojie; Bi Xiangang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper presents a group interaction method based on Wireless Sensor Network which supplies new attempts and ideas for human-computer interaction. Firstly, analyze group interaction framework that is different from the monomer interaction, then integrate data language of group interaction based on user’s purpose so that the Wireless Sensor Network technology and methods are applied to the system of group interaction. Finally, group interaction toys based on Wireless Sensor Network are developed. Each of toy monomers is compactly filled with sensors, wireless communication devices, LED lights. The Wireless Sensor Network which is composed of many monomers makes interface function come true in virtual. The users not only act on the physical object but also act directly on the "data" when they use the device. Currently the functions including light transmission and light color blending have been accomplished and developing. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2700